Translation and Modernization in East Asia in the Nineteenth and Early Twentieth Centuries - Wong, Lawrence Wang-chi (Asian translation traditions series, 2018)
This volume aims at studying the role played by translation in the modernization process of the East Asian countries. In the nineteenth and early twentieth centuries, many people saw the West as a model for modernization and hence modernization in East Asia was more often than not taken as a process of learning from or even imitating the West. In this process, translation played a crucial role, when efforts were made to import Western ideas, knowledge, concepts, and practices. The papers in this volume study and explain the various translation phenomena in the modernization processes of China, Korea, and Japan.